Identification of a new hexadentate iron chelator capable of restricting the intramacrophagic growth of Mycobacterium avium - Sofia Sousa Fernandes (2010)
Iron accumulation has been suggested to contribute to an increase of the susceptibility to mycobacterial infections. In this study we tested the effect of an array of iron chelating ligands of the 3-hydroxy-4-pyidinone family, in the intramacrophagic growth of Mycobacterium ovum, We found that bidentate chelators, namely N-alkyl-3-hydroxy-4-pyrichnones and N-aryl-3-hydroxy-4-pyndinones, did not affect the growth of M avium inside mouse macrophages In the case of the hexadentate chelators, those synthesized using an alkylamine (CP262) or a benzene ring (CP252) to link the three bidentate units, did not have an inhibitory effect on intramacrophagic growth of M (mum while those synthesized from a tripodal structure to anchor the bidentate units were capable of inhibiting the intramacrophagic growth of M. (MUM The molecule we designated CP777 had the strongest inhibitory activity The growth-reducing activity of CP777 was abrogated when this molecule was saturated with iron These results confirm that iron deprivation, by the use of iron chelating compounds, restricts M ovum growth and that new iron chelators offer an approach to controlling mycobacterial infections